2015
DOI: 10.1038/srep13088
|View full text |Cite
|
Sign up to set email alerts
|

Sub-0.5 V Highly Stable Aqueous Salt Gated Metal Oxide Electronics

Abstract: Recently, growing interest in implantable bionics and biochemical sensors spurred the research for developing non-conventional electronics with excellent device characteristics at low operation voltages and prolonged device stability under physiological conditions. Herein, we report high-performance aqueous electrolyte-gated thin-film transistors using a sol-gel amorphous metal oxide semiconductor and aqueous electrolyte dielectrics based on small ionic salts. The proper selection of channel material (i.e., in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…57 Figure 2c shows that I D and g m increased with increasing V Ag/AgCl and the maximum g m value of 9.38 mS was obtained at a drain voltage bias of 0.5 V at V Ag/AgCl = 0.472 V. We extracted a µ FE of 18 cm 2 V -1 s -1 from electrolyte-gated driving, which was impressive, considering its simple process and superiority to other electrolyte-gated oxide FETs that have been reported. [57][58][59][60][61][62][63][64] Quasi-2D metal oxide FETs have several properties and advantages. First, due to the nature of solution processing regarding solvent evaporation and precursor decomposition, nanopores are 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 left behind in the film during deposition, typically.…”
Section: Resultsmentioning
confidence: 97%
“…57 Figure 2c shows that I D and g m increased with increasing V Ag/AgCl and the maximum g m value of 9.38 mS was obtained at a drain voltage bias of 0.5 V at V Ag/AgCl = 0.472 V. We extracted a µ FE of 18 cm 2 V -1 s -1 from electrolyte-gated driving, which was impressive, considering its simple process and superiority to other electrolyte-gated oxide FETs that have been reported. [57][58][59][60][61][62][63][64] Quasi-2D metal oxide FETs have several properties and advantages. First, due to the nature of solution processing regarding solvent evaporation and precursor decomposition, nanopores are 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 left behind in the film during deposition, typically.…”
Section: Resultsmentioning
confidence: 97%
“…Sol-gel synthesis is a traditional method to prepare various inorganic solids (typically oxides) starting from a solution-phase chemical precursor [47,48]. Recently, solgel-derived functional oxide thin films have gained a tremendous attention for their integration in practical electronic devices [49][50][51][52][53]. Especially, the combination of an intrinsically high k diel , structural robustness, and solution-processability of sol-gel metal-oxide dielectrics is a highly promising strategy for realizing low-voltage OFETs on flexible substrates.…”
Section: Sol-gel Metal Oxidesmentioning
confidence: 99%
“…Solution-processable In-Ga-Zn-O compounds (IGZO) are promising n-type semiconductors for printed large-area electronics [ 73 , 74 , 75 ]. Dai et al demonstrated transparent IGZO-graphene mixed channel based high-performance FETs ( Figure 15 ) [ 76 ].…”
Section: Advances In Nanostructured Devicesmentioning
confidence: 99%